1, 25 dihydroxyvitamin D3 inhibits the proliferation of thyroid cancer stem-like cells via cell cycle arrest. (2nd April 2016) - Peng, Wen; Wang, Kun; Zheng, Rendong; Derwahl, Michael
ABSTRACT: Background: An anti-proliferative effect of vitamin D has been reported in different carcinomas, including thyroid cancer. Cancer stem cells (CSCs), a very small fraction of cancer cells, are widely believed to be responsible for cancer initiation, relapse and metastasis.Objectives: We addressed the question as to whether CSCs derived from the anaplastic thyroid carcinoma cell lines SW1736, C643, HTh74 and its doxorubicin- resistant subline HTh74R are also a target of vitamin D action. Methods: The effect of calcitriol on growth of HTh74, HTh74R, SW1736 and C643 cell lines was investigated by cell viability assays. In stem-enriched cells derived from thyro-spheres cell cycle analysis and apoptotic assays were performed. Furthermore, the role of calcitriol in the formation of cancer thyro-spheres and its putative differentiation-inducing effect were analysed.Results: CSCs isolated as thyro-spheres from all the four anaplastic thyroid carcinoma cells expressed vitamin D receptors as did their parental cells. Calcitriol inhibited proliferation of anaplastic thyroid carcinoma cells with a more pronounced effect on doxorubicin-resistant HTh74R cells, and it significantly reduced the capacity to form stem cell-derived spheres and decreased the size of these spheres that consist of CSCs and their progenitor cells. As revealed by cell cycle analysis, calcitriol induced G2/M phase arrest in thyro-sphere cells derived cells from HTh74, HTh74R and C643 but did not affect apoptosis. Finally, calcitriol altered morphology of CSCs.Conclusion: Calcitriol inhibited the growth of CSCs derived from anaplastic thyroid cancer cells. It may also exert a pro-differentiation effect in thyroid CSCs.